HISTOPATHOLOGICAL EFFECTS OF BISPHENOL-A ON LIVER, KIDNEYS AND GILLS OF INDIAN MAJOR CARP, CATLA CATLA (HAMILTON, 1822) - M. Faheem; N. Jahan; K. P. Lone (Journal of Animal and Plant Sciences, 2016)
Bisphenol-A (BPA) is a xenoestrogen that mimics the action of natural estrogen, estradiol-17β, and can disrupt the endocrine system. Present study was designed to investigate histopathological effects of BPA on some vital organs of major carp, Catla catla. Fish were exposed to various sub-lethal concentrations (1 to 4 ppm) of BPA in a semi-static system for 15 days.  After the stipulated time, liver, kidneys and gills were dissected out and fixed immediately in 10 % buffered formalin. After embedding in paraffin wax, 5 micron thick sections were cut and stained with H & E and PAS stains.  In liver, BPA caused central vein congestion, inflammation, edema, degeneration and necrosis of hepatocytes. Kidney anomalies included obliteration of bowmen’s space, shrinkage and degeneration of tubules and glomerulus. Gills responded to BPA stress by hyperplasia of mucous cells, clubbing and degeneration of secondary-lamellae. The present study revealed that BPA causes degenerative changes in various vital organs of C. catla and severity of histological changes were dose-related.
Keywords: Histopathology; Endocrine disrupting chemicals; Bisphenol-A; Catla catla